Automated, high-accuracy classification of textured microstructures using a convolutional neural network - Khurjekar, Ishan D.; Conry, Bryan; Kesler, Michael S.; Tonks, Michael R.; Krause, Amanda R.; Harley, Joel B. (Frontiers in Materials, 2023)
Crystallographic texture is an important descriptor of material properties but requires time- intensive electron backscatter diffraction (EBSD) for identifying grain orientations. While some metrics such as grain size or grain aspect ratio can distinguish textured microstructures from untextured microstructures after significant grain growth, such morphological differences are not always visually observable. This paper explores the use of deep learning to classify experimentally measured textured microstructures without knowledge of crystallographic orientation. A deep convolutional neural network is used to extract high-order morphological features from binary images to distinguish textured microstructures from untextured microstructures. The convolutional neural network results are compared with a statistical Kolmogorov–Smirnov tests with traditional morphological metrics for describing microstructures. Results show that the convolutional neural network achieves a significantly improved classification accuracy, particularly at early stages of grain growth, highlighting the capability of deep learning to identify the subtle morphological patterns resulting from texture